Fluid ingestion strategies of competitive cyclists during 40 km time trial competition - Backx, K.; Howatson, G.; van Someren, K. A. (Journal of Sports Science & Medicine, 2007)
Loss of fluid during prolonged exercise has been purported to be a cause of fatigue (Below et al., 1995; Walsh et al., 1994, for example). A plethora of information regarding `optimal` fluid replacement strategies exists; perhaps the most prominent of these in the public domain is the position stand on exercise and fluid replacement published by the American College of Sports Medicine (ACSM). It recommends that one should ingest fluid early and continually at regular intervals in an attempt to replace the volume of fluid lost through sweating or consume as much as can be tolerated (Covertino et al., 1996). Drinking practices associated with different types of endurance activity are not well documented and it may be possible that the guidelines based on empirical data derived from laboratory conditions lack the necessary ecological validity for performance in the field. To our knowledge, there are no data on fluid intake or body mass losses during high-intensity cycling time trials (TT) outside of laboratory conditions; although a pilot study questionnaire used by El-Sayed et al. (1997) revealed that the volume ingested in pre-race preparation over a similar TT race distance (46 km) ranged between 0.125-0.5 L. Therefore the aim of this investigation was to elucidate the fluid ingestion strategies of competitive cyclists during pre-race preparation and 40 km TT competition and the resultant body mass loss.